The association between dietary inflammation index and bone mineral density: results from the United States National Health and nutrition examination surveys - Siyao Li; Mengru Zeng (Renal Failure)
Objective To investigate the associations of dietary inflammation index (DII) with bone density and osteoporosis in different femoral areas.Methods The study population was selected from the National Health and Nutrition Examination Survey (NHANES) with the exclusion criteria of age 18, pregnancy, or missing information on DII, femoral bone marrow density (BMD), estimated glomerular filtration rate (eGFR), and urine albumin-to-creatinine ratio (UACR), or had diseases which may influence systemic inflammation. DII was calculated based on the questionnaire interview of dietary recall within 24 h. Subjects’ baseline characteristics were collected. The associations between DII and different femoral areas were analyzed.Results After applying exclusion criteria, 10,312 participants were included in the study. Significant differences among DII tertiles were found in BMD or T scores (p < .001) of the femoral neck, the trochanter, the intertrochanter, and the total femur. High DII was associated with low BMDs and T scores in all the femoral areas (all p < .01). Compared to low DII (tertile1, DII < 0.380 as reference), in the femoral neck, the intertrochanter, and the total femur, increased DII is independently associated with increased the possibility of the presence of osteoporosis (OR, 95% CI: 1.88, 1.11–3.20; 2.10, 1.05–4.20; 1.94, 1.02–3.69, respectively). However, this positive association was only observed in the trochanteric area of the non-Hispanic White population after full adjustment (OR, 95% CI: 3.22 (1.18, 8.79)). No significant difference in the association of DII and the presence of osteoporosis were found in subjects with or without impaired kidney function (eGFR < 60 ml/min/1.73 m2).Conclusion High DII is independently related to declined femoral BMD of femoral areas.